2000
DOI: 10.1007/s002230010078
|View full text |Cite
|
Sign up to set email alerts
|

Bone Sialoprotein (BSP) is a Crucial Factor for the Expression of Osteoblastic Phenotypes of Bone Marrow Cells Cultured on Type I Collagen Matrix

Abstract: In this study, we demonstrated that type I collagen matrix induced the expression of osteoblastic phenotypes of bone marrow cells, and that antibone sialoprotein (BSP) monoclonal antibody suppressed the expression of these phenotypes. On the other hand, BSP accelerated the expression of osteoblastic phenotypes of bone marrow cells. The adherent bone marrow cells were harvested from rat femur and cultured on type I collagen matrix gels in medium containing 15% fetal calf serum, neither beta-glycerophosphate nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 44 publications
2
54
0
2
Order By: Relevance
“…In particular, cells lining the bone surface showed stronger expressions. The interaction between the cells on the bone surface and bone matrix molecules, such as type I collagen (Jikko et al, 1999;Takeuchi et al, 1996Takeuchi et al, , 1997, fibronectin (Moursi et al, 1997), osteopontin (Liu et al, 1997) or bone sialoprotein (Mizuno et al, 2000) may be involved in osteoblastic differentiation, since it has been suggested that the bone matrix molecules are recognized by the integrin receptors of osteoprogenitors and promote osteoblastic differentiation via activation of the focal adhesion kinase and its downstream signals (Takeuchi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cells lining the bone surface showed stronger expressions. The interaction between the cells on the bone surface and bone matrix molecules, such as type I collagen (Jikko et al, 1999;Takeuchi et al, 1996Takeuchi et al, , 1997, fibronectin (Moursi et al, 1997), osteopontin (Liu et al, 1997) or bone sialoprotein (Mizuno et al, 2000) may be involved in osteoblastic differentiation, since it has been suggested that the bone matrix molecules are recognized by the integrin receptors of osteoprogenitors and promote osteoblastic differentiation via activation of the focal adhesion kinase and its downstream signals (Takeuchi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that as little as 9 nM BSP is required to nucleate HA, and recently the overexpression of BSP in osteoblasts has been shown to enhance mineralisation (Hunter et al 1996, Gordon et al 2007. Similarly, osteoblast cultures grown in the presence of an anti-BSP antibody exhibit reduced mineralisation (Cooper et al 1998, Mizuno et al 2000. This nucleation potency is increased on BSP binding to collagen, suggesting a cooperative relationship (Baht et al 2008).…”
Section: Bone Sialoproteinmentioning
confidence: 99%
“…The coupling of the state of phosphorylation of BSP with that of OPN in regulating the rate of calcium phosphate deposition pre- sents a unique biological interrelationship between these two proteins. Other studies have indicated that BSP promotes mineral deposition in cell cultures (9,43) and differentiation of bone marrow cells to osteoblasts (44). Additional in vivo work using implants of native bone BSP-collagen composites in bone repair (19) and reparative dentinogenesis (7, 8, 20 -22) elaborated on the multifunctional capacity of this protein.…”
Section: (Les(p)deengvfk) Residues 42-62 (Favqsssdss(p)eengngds(p)s(mentioning
confidence: 99%